DANCE AS A SOCIAL GIFT: A STUDY OF MARCEL MAUSS'S THEORY OF THE GIFT IN PERFORMING ARTS PRACTICE: DANCE AS A SOCIAL GIFT: A STUDY OF MARCEL MAUSS'S THEORY OF THE GIFT IN PERFORMING ARTS PRACTICE - Aidah, Hasna; Nursilah, Nursilah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This article discusses the relevance of Marcel Mauss's The Gift theory in understanding dance as aform of symbolic exchange in the context of performing arts. Based on a conceptual study and aperformance anthropology approach, this paper highlights the main principle in Mauss's theory,namely the obligation to give, receive, and reciprocate, which can be interpreted as a social structurethat binds the relationship between dancers, audiences, and society. In dance practice, the act ofdancing is seen as a